Modification of magnetite extracted from mill scales waste with CTAB and chitosan for cadmium ions removal from aqueous solution - Ahmad Nazri, Nur Asyikin (2021)
The goal of this research is to improve the stability of magnetite recovered from millscales waste (MSW) by modifying it with Cetyltrimethyleammonium Bromide (CTAB) and Chitosan (Chi) for use in Cd(II) removal from aqueous solution. Magnetite was subjected to High Energy Ball Milling (HEBM) for 5 distinct milling hours, namely 4, 8, 12, 16, and 20 hours, before being modified with the CTAB and Chi. From the characterization results there were found that the characteristics on magnetite milled for 8 h obviously more stable (±10.9 mV) and had highest ability in removing the cadmium ions. Therefore, M8 was chosen to be modified with CTAB and Chi. As the results, the stability of the modified MNS (M8-CTAB and M8-Chi) had enhanced from -10.9 to -39.5 and -48.5 mV respectively. This was supported with the high-resolution transmission electron microscopy (HRTEM) images that shows higher dispersion after the modification. The higher dispersion occurred was successfully enhanced the surface area from 2.58 to 19.19 and 22.49 m2 g-1 for M8- CTAB and M8- Chi respectively. The magnetic saturation had reduced due to the modification which became 32.16 and 31.91 emu g-1 after the modification with CTAB and chitosan respectively. Meanwhile, the magnetic saturation before the HEBM is 20.58 emu g-1 and increased to 50.36 emu g-1 . Fourier transform infrared (FTIR) spectrum shows the appearance of functional groups such -CH, -NH, -COO, and -OH contributed from CTAB and Chi which proved the success modification through the heterocoagulation (self-assembly) method. The adsorption properties obeyed the Langmuir isotherm model and the maximum uptake of the Cd(II) from the solution onto the M8, M8-CTAB, and M8-Chi is 10.31, 26.70 and 30.86 mg g-1 respectively. Regeneration results for MNS showed small reduced on the performance as the cycles used in Cadmium removal for 5 time (1st cycle, 98%, 5th cycle 92%). The regeneration performance suggests the sustainability of the magnetic nanosorbent (MNS) to be used in industries. The best MNS (M8-Chi2) in this works manage to remove for about 98.6% (2.96 mg L-1) of the initial 3 mg L-1 Cd(II) which indicated that it able to remove the Cd(II) more than the permissible Cd(II) level in drinking water (0.5 μg L-1). The M8-Chi2 MNS also characterized with XPS in order to confirm the adsorption of Cd(II) perfectly occurs onto it. Interestingly, it was found that the XPS spectrum showed the peak for the Cd(II) on the MNS after the adsorption. From this works, it can be concluded that the prepared MNS (M8-Chi2) can be a promising advanced adsorbent in environmental pollution clean-up.